Causal reasoning in medical imaging - Vlontzos, Athanasios; Müller, Christine; Kainz, Bernhard (Trustworthy AI in Medical Imaging, 2025)
Medical image analysis is a vibrant research area that offers doctors and medical practitioners valuable insight and the ability to accurately diagnose and monitor disease. Machine learning provides an additional boost for this area. However, machine learning for medical image analysis is particularly vulnerable to natural biases like domain shifts that affect algorithmic performance and robustness. This chapter analyzes machine learning for medical image analysis within the framework of Technology Readiness Levels and reviews how causal analysis methods can fill a gap when creating robust and adaptable medical image analysis algorithms. This work provides a review of the methods using causality in medical imaging AI/ML, and highlights the potential of causal analysis to mitigate critical problems for clinical translatio